Paradox And Theorizing Within The Resource-Based View - Lado, Augustine A.; Boyd, Nancy G.; Wright, Peter; Kroll, Mark (Academy of Management Review, 2006)
By working with and through the paradoxes present in the resource-based view (RBV) of strategic management, scholars can advance understanding concerning the con-tradictions and tensions inherent in creating and sustaining superior firm perfor-mance. We identify and discuss various RBV paradoxes, illustrating how paradoxical thinking can enhance theorizing and open up new vistas for knowing and understand-ing. Finally, we discuss the utility of the paradoxical perspective in furthering RBV scholarship. Paradox, “the dynamic tensions of juxtaposed opposites ” (Rosen, 1994: xvii), underpins much organization and management scholarship and practice. The use of paradox can promote diver-gent or “oppositional ” thinking (Cameron, 1986;